Schools’ Readiness, Teachers’ Proficiency, and Science Technology Engineering and Mathematics (STEM) Students’ Preparedness for Higher Education - Moleta, Niña M.; Yango, Antonio R. (Technium Social Sciences Journal, 2023)
Students’ preparedness is the extend to which students possess the skills, knowledge, and disposition necessary to succeed academically and socially in higher education practices. The purpose of this study was to determine schools’ level of readiness along funding resources, teacher training and curriculum, and teachers’ level of proficiency along pedagogies, qualification and training, classroom instruction and adequate resources, and STEM students’ level of preparedness for higher education and test the significant difference between the different factors that influence students’ preparedness for higher education. The researcher utilized descriptive-correlational method of research with the help of survey questionnaires as the main source of data. A value of 0.000 indicates a high level of the predictions of the dependent variable (STEM students’ preparedness for higher education). Further, the ANOVA shows that that the independent variable curriculum under the school readiness being statistically significantly predicted the dependent variable STEM student’s preparedness with an F-value of 6.331 and probability value of 0.000 which is less than the 0.05 significance level. This study is hoped to be a useful reference in sustaining schools’ readiness in terms of curriculum design. Curriculum defined as a complex, dynamic, and contested entity that is not limited to a prescribed set of content or outcomes, but it shaped by various actors and forces, including policy, culture, history, and social context.